BİLİŞİM TEKNOLOJİLERİ VE YAZILIM DERSİ ÖĞRETİM PROGRAMININ TEKNOLOJİ OKURYAZARLIĞI BOYUTLARI AÇISINDAN İNCELENMESİ. - Debbağ, Murat; Fidan, Mustafa (Mehmet Akif Ersoy University Journal of Education Faculty, 2019)
The purpose of this study is to evaluate the goals of Information Technologies and Software (ITS) curriculum within the framework “technology literacy” dimensions. In this context, firstly according to experts’ opinions, the dimensions of technology literacy have been revealed at national and international level and the goals have been examined in terms of these dimensions. Two-stage Delphi method was used in this study. Criteria sampling, being from purposeful sampling method, was used by selecting the experts. The study group of the study is composed of 9 experts. As a result of the research, five dimensions were determined as “the origin of technology”, "the effect of technology on human life", "applicability", "production and design", "evaluation and sustainability". It has been concluded that among these dimensions, the reflections of "the effect of technology on human life” and "evaluation and sustainability" are mostly inadequate on the goals of the curriculum. Moreover, the objectives regarding not only the historical progress and development of basic concepts such as computer, internet, programming and software in terms of the aspect of "foundations of technology" but also the design principles, creativity and technological product development in terms of the aspect of “production and design" have been found to be insufficient. In this study, the proposals for future studies and curriculum developers were included in the study.